On M-ideals in B(∑i=1∞⊗pℓrni) - Chong-Man Cho (International Journal of Mathematics and Mathematical Sciences)
For 1<p, r<∞, X=(∑i=1∞⊗pℓrni), {ni} bounded, the space K(X) of all compact operators on X is the only nontrivial M-ideal in the space B(X) of all bounded linear operators on X.